2014
DOI: 10.1021/jf5036355
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Chemical Profiling and Antioxidant Activities of Fruits, Leaves, Branches, and Flowers of Citrus grandis ‘Tomentosa’

Abstract: Citrus grandis 'Tomentosa' (CGT) is particularly cultivated in China and widely used in health foods. In this study, the chemical profiles of different parts of CGT were comprehensively compared by rapid resolution liquid chromatography coupled to electrospray ionization quadrupole time-of-flight mass spectrometry method. A total of 22 compounds were identified and two C-glucosyl flavones were found for the first time in CGT. Four main constituents (rhiofolin, naringin, meranzin hydrate, and isoimperatorin) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 30 publications
2
25
0
1
Order By: Relevance
“…The phytochemicals were extracted according to previously published literature. [8] In summary, 0.5 g of the sample was extracted in 25 mL of methanol by an ultrasonicator for 30 min at 100 Hz. After centrifugation, the supernatant was filtrated and stored at −20°C before analysis.…”
Section: Plant Materials and Sample Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The phytochemicals were extracted according to previously published literature. [8] In summary, 0.5 g of the sample was extracted in 25 mL of methanol by an ultrasonicator for 30 min at 100 Hz. After centrifugation, the supernatant was filtrated and stored at −20°C before analysis.…”
Section: Plant Materials and Sample Treatmentmentioning
confidence: 99%
“…[5] In recent years, the bioactivities of CGT, such as its antioxidant, anticancer, antimicrobial and anti-inflammatory properties, have also been discovered and investigated. [6][7][8][9] The exocarp of CGT is densely pubescent, which is a trait of ancient species. [10] The dense, short and firm trichomes on the surface of the fruits and leaves can reduce the chance of being infected by Candidatus Liberibacter, which causes the citrus greening disease (Huanglongbing), a fatal disease for the citrus industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, a lot of researches have been focused on the chemical constituents of Citrus species, especially the flavonoids (Duan and others ; Rodríguez‐Rivera and others ). For example, Zheng identified 41 chemical compounds in Citri Reticulatae Pericarpium utilizing rapid resolution liquid chromatography‐electrospray ionisation tandem mass spectrometry (RRLC‐ESI‐MS/MS) (Zheng and others ).…”
Section: Introductionmentioning
confidence: 99%
“…Moringa oleifera has traditionally been used in the treatment of malaria, parasitic diseases, skin diseases, hypertension and diabetes. It has been demonstrated that Moringa oleifera exhibits pharmacological properties such as antioxidant [8], anti-inflammatory, anti-cancer, anti-hyperglycemic and anti-hyperlipidemic properties [2]. Leone et al have reviewed the cultivation, genetics, ethnopharmacology, phytochemistry and pharmacology of Moringa oleifera [1], whereas the health benefits and medicinal use of Moringa oleifera has been reviewed by Abdull Razis et al [2] and Anwar et al [3].…”
Section: Introductionmentioning
confidence: 99%